미역쇠(Endarachne binghamiae)추출물의 멜라닌 생성 억제 효과 - 전영식; 정유정; 염종경; 김용기; 김수남 (한국자원식물학회, 2013)
In this study, we investigated the effect of 88 marine algae extracts on melanin synthesis to develop newwhitening agents. Among varieties of marine algae tested, the ethyl acetate extracts from Endarachne binghamiae (EB),Scytosiphon lomentaria, Sargassum yezoense, Ecklonia cava and Sargassum fusiforme inhibited melanin synthesis inmelan-a cells. EB treatment showed the strongest inhibitory activity in melanin synthesis, compared with that of otherextracts. EB-mediated inhibition of melanin synthesis appeared to be associated with inhibition of α-glucosidase-dependentglycosylation of tyrosinase in melan-a cells. In addition, EB treatment did not affect mushroom tyrosinase or cell-extractedtyrosinase activity in vitro. Taken together, our findings suggest that anti-browning effect of EB on skin is mediated throughregulation of α-glucosidase activity and subsequent inhibition of tyrosinase activity and melanin synthesis, and furtherdevelopment of EB as a potential agent for skin whitening.